2017
DOI: 10.21093/di.v17i1.815
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Language Anxiety in Academic Writing

Abstract: This study is aimed to investigate Foreign Language Anxiety (FLA) in academic writing specifically to EFL students at university level. The factors that cause the students feel anxious in English writing represent on close-ended questionnaires that the researcher asks the students to answer. In addition, the researcher does direct observation by acting as a passive observer where she has no role in conducting or helping the lecturer in teaching the writing course. In this case, what the researcher does is find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 15 publications
3
14
0
2
Order By: Relevance
“…Referring to the study from Rezaei & Jafari (2014), feedback from the lecturer played an important role in improving the students' writing ability. That study is also supported by a research from Ariyanti (2017), where she found that in High Anxiety Level was indicated from the apprehension of obtaining negative comment from the lecturer. Furthermore, another study related to the importance of feedback came from Ahmadi, Maftoon, & Mehrdad (2012).…”
Section: Introductionsupporting
confidence: 66%
“…Referring to the study from Rezaei & Jafari (2014), feedback from the lecturer played an important role in improving the students' writing ability. That study is also supported by a research from Ariyanti (2017), where she found that in High Anxiety Level was indicated from the apprehension of obtaining negative comment from the lecturer. Furthermore, another study related to the importance of feedback came from Ahmadi, Maftoon, & Mehrdad (2012).…”
Section: Introductionsupporting
confidence: 66%
“…To address the research question of the type of anxiety most respondents suffered from, the data of questionnaire were grouped into Somatic Anxiety, Cognitive Anxiety, and Avoidance Behaviour which were based on the items of the questionnaire. Somatic anxiety was indicated by items number 2,9,11,13,15,17,18,20,22, and 23 (10 items), cognitive anxiety was indicated by items number 1, 3, 5, 10, 16, 17, 19, 24, 25, and 27 (10 items), and avoidance behaviour was indicated by items 2, 4, 6, 8, 12, 14, 26 (7 items).…”
Section: A the Resultsmentioning
confidence: 99%
“…Language anxiety, defined as a kind of subjective feeling of tension, apprehension, nervousness, and worries which very often arouses automatically from the nervous system [1], has become one of the major problems faced by Indonesian learners in the effort to master English. The study of Ariyanti for example found that many learners were suffering from a high level of writing anxiety [2]. Another study as written by Wahyuni and Umam also found out that more than half of their research respondents suffered from a high writing anxiety [3].…”
Section: Introductionmentioning
confidence: 98%
“…Hence, by doing this technique, students" confidence to write an English essay will be increased and their writing anxiety will be decreased [26]. It is true because the complex process of producing a qualified writing is starting from content up to grammatical aspects are potential to drive the students to high anxiety level [27]. Therefore, it is important to note that giving feedback is not merely judging whether the students go wrong in writing, but it tends to a matter of guidance and making the students comprehend on how to deal with their misconception.…”
Section: Errors That Commonly Appeared In Students' Essaysmentioning
confidence: 99%